2003
DOI: 10.1111/j.1532-5415.2004.52018.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depression on Diagnosis, Treatment, and Survival of Older Women with Breast Cancer

Abstract: OBJECTIVES-To assess the effect of a prior diagnosis of depression on the diagnosis, treatment, and survival of older women with breast cancer. DESIGN-Retrospective analysis of records from Surveillance, Epidemiology and End Results (SEER) and Medicare claims. SETTING-Registries from seven major cities and five states.PARTICIPANTS-A total of 24,696 women aged 67 to 90 diagnosed with breast cancer between 1993 and 1996 and included in the SEER Medicare linked database were studied.MEASUREMENTS-Information on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
188
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(204 citation statements)
references
References 40 publications
(72 reference statements)
13
188
0
3
Order By: Relevance
“…In an earlier study using a population-based sample, neuroticism was reported to be a significant risk factor for major depression (Kendler et al, 2004). Furthermore, a number of prospective studies have reported a statistically significant association between depression (higher degree of depressive symptoms or psychiatrically diagnosed depression) and survival in patients with various types of cancer (Hjerl et al, 2003;Goodwin et al, 2004). The association between depression and cancer survival could be explained by potential intermediaries such as endocrinological or immunological pathways (Pettingale et al, 1981;Kiecolt-Glaser and Glaser, 1999;Spiegel and Kato, 1996), or by compliance with cancer treatment (Holland, 1987;Colleoni et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study using a population-based sample, neuroticism was reported to be a significant risk factor for major depression (Kendler et al, 2004). Furthermore, a number of prospective studies have reported a statistically significant association between depression (higher degree of depressive symptoms or psychiatrically diagnosed depression) and survival in patients with various types of cancer (Hjerl et al, 2003;Goodwin et al, 2004). The association between depression and cancer survival could be explained by potential intermediaries such as endocrinological or immunological pathways (Pettingale et al, 1981;Kiecolt-Glaser and Glaser, 1999;Spiegel and Kato, 1996), or by compliance with cancer treatment (Holland, 1987;Colleoni et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with depression displayed three times greater odds to be noncompliant with medical treatment recommendations compared with those who were not depressed 31. And a study in breast cancer demonstrated that women patients with depression were less likely to accept surgery 32. Physicians should pay more attention to those unmarried and diagnosed with GC, and recommen them for psychologist's help if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a well-recognized risk factor for poor medication-taking behavior 34,35 and the link between depression and early discontinuation of tamoxifen has been noted previously. 15 Depression has also been associated with reduced survival in women with breast cancer, [36][37][38] although the evidence from some studies has been inconclusive. 39 Whereas a number of mechanisms have been proposed to explain this association, results from this study suggest that nonpersistence with tamoxifen may in part provide an explanation.…”
Section: Discussionmentioning
confidence: 99%